2022
DOI: 10.3390/biom12060760
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phytoestrogen Intake and Cognitive Status in Southern Italian Older Adults

Abstract: Background: Aging society faces significant health challenges, among which cognitive-related disorders are emerging. Diet quality has been recognized among the major contributors to the rising prevalence of cognitive disorders, with increasing evidence of the putative role of plant-based foods and their bioactive components, including polyphenols. Dietary polyphenols, including phytoestrogens, have been hypothesized to exert beneficial effects toward brain health through various molecular mechanisms. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
5
0
1
Order By: Relevance
“…[ 3 , 4 , 5 ]. Although many interventions have been used clinically to slow the progression of aging-related diseases, their effectiveness is still limited [ 6 , 7 ]. Therefore, a better understanding of the molecular mechanisms of the aging process and identification of aging biomarkers and possible therapeutic targets for ARDs is performed to pave the way for future research on aging biology and new antiaging therapies.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 , 4 , 5 ]. Although many interventions have been used clinically to slow the progression of aging-related diseases, their effectiveness is still limited [ 6 , 7 ]. Therefore, a better understanding of the molecular mechanisms of the aging process and identification of aging biomarkers and possible therapeutic targets for ARDs is performed to pave the way for future research on aging biology and new antiaging therapies.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1823 studies were identified through the search strategy ( Figure 1 ). Out of these, after examination of the title ( n = 1303) and abstract ( n = 521) and full texts ( n = 487), 37 articles [ 15–51 ] were included in this review. The main characteristics of the included studies are presented in Table S2, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…[ 34 ] Another study conducted on the same sample showed that higher intake of isoflavones, but not lignans, were inversely associated with cognitive impairment (T3 vs T1, OR = 0.46, 95% CI: 0.21, 1.00 and OR = 0.84, 95% CI: 0.41, 1.71, respectively), but both groups of molecules resulted associated when the analysis was restricted to older individuals (>70 years) (T3 vs T1, OR = 0.10, 95% CI: 0.01, 0.88 and OR = 0.16, 95% CI: 0.03, 0.87, respectively). [ 35 ] A more recent prospective study including 16 704 older participants from the Singapore Chinese Health Study (SCHS) followed up for about 11 years showed a significant inverse association between flavonoid intake (except for flavanones) and cognitive impairment assessed through a Singapore‐Modified version of the MMSE. Taking into consideration flavonoid consumption, the odds of cognitive decline for the highest versus the lowest quartile of intake was 0.77 (95% CI: 0.68, 0.88).…”
Section: Resultsmentioning
confidence: 99%
“…A recordação e a precisão são ainda mais propensas a serem comprometidas em populações idosas, levando a estimativas imprecisas da ingestão alimentar quando as avaliações dependem de auto-relato 18,19 . A maior adesão aos padrões alimentares à base de plantas e o alto consumo de alimentos de origem vegetal, como vegetais, frutas, leguminosas e grãos integrais, são úteis para preservar e fortalecer a saúde cognitiva 19 .…”
Section: Os Estudos Incluídos Utilizaram Ounclassified